Libel and the media - Eric Barendt (Clarendon Press,Oxford University Press, 1997)
The impact of libel law on the freedom of the press is a subject which interests not only practicing media lawyers, law students, and journalists, but also members of the general public who are keen to learn about any perceived threat to the freedom of the press. This book presents all those people with an accessible and jargon-free look at the impact of libel law on the media. It is based on research conducted by Professor Barendt and his collaborators which involved interviewing the editors of national newspapers, journalists, and their lawyers to discover the extent to which libel laws chill press freedom.